Nocturnal Light Pollution Synergistically Impairs Glucose Metabolism With Age and Weight in Monkeys - Shuxing Wang; Xuange Cheng; Zihao Liang; Zhenyi Chen; Jiankai Zhang; Qiang Xu (Journal of Diabetes Research)
Over the past decades, the global prevalence of Type 2 diabetes mellitus (T2D) and impaired glucose tolerance (IGT) has been increasing at an epidemic rate, yet the exact cause remains unknown. It is widely accepted that glucose metabolism can be impaired by circadian rhythms and sleep disturbances. Concurrently, exposures to light at night have been closely linked to circadian and sleep disturbances. However, there is no direct experiment on primates to demonstrate the precise extent of how serious light pollution impairs glucose metabolism, whether people will eventually become accustomed to this environment, and whether the pollution has synergistic impairing effects with aging and weight on glucose metabolism. To quantitatively address these questions, 137 cynomolgus were exposed to three distinct nocturnal light intensities for consecutive 10 months. Monthly glucose metabolism assessments were conducted. Data pertaining to the mortality rate of preexisting diabetes, incidence of light-induced diabetes and IGT, and alterations in insulin secretion were collected and analyzed. The results show that nocturnal light (1) caused premature deaths in individuals with preexisting diabetes; (2) intensity-dependently induced diabetes and IGT in previous healthy monkeys; (3) intensity-dependently reduced melatonin secretion; (4) had a synergistic impairing effect on glucose metabolism with aging and weight; and (5) although monkeys would eventually adapt to the environment, the disrupted glucose metabolism would not fully recover in most individuals. In conclusion, nocturnal light is associated with the global high prevalence of T2D and IGT. The harmful effects of light pollution on glucose metabolism are synergistic with age and weight.